Voice of the Old Wolf : Lucullus Virgil McWhorter and the Nez Perce Indians - Evans, Steven Ross, 1943- (Book collections on Project MUSE., 2017)
Lucullus V. McWhorter devoted much of his life to preserving the history of the Nez Perce and Yakama Indians of the Pacific Northwest's interior plateau region. McWhorter held a unique role as Nez Perce tribal historian and gatherer of tradition lore from both treaty and non-treaty bands. In Voice of the Old Wolf, Steve Evans helps to fill a gap in Nez Perce history, focusing on the 1880s to the 1940s, a period often neglected by the many historians of the 1877 war. --From publisher's description.